The Influence of Social Media Advertising on Purchasing Decisions at Startup Companies - Dany Perdana Sitompul; Ferawati Ferawati (Almana : Jurnal Manajemen dan Bisnis, 2021)
The era of globalization, better known as the Industrial Revolution, Era 4.0, makes all sectors change. We are starting to see massive efficiency where output becomes one of the targeted indicators. The maximum disclosure of information with almost free access can be a huge opportunity for a company to startups compete on a wide scale. Marketing is an activity that should always be included, from everything carried out by large companies to Startups or SMEs. In this new era, marketing is generally executed out in two ways, traditional and digital. We also know that social media is an individual quite widely used for personal and business purposes. And the use of this new digital trend in marketing has also greatly increased, becoming the media used by almost every company or startup in carrying out its marketing campaigns. The specific purpose of this research is to understand the true impact of social media marketing and how effective this marketing is in the era of industrial revolution 4.0. This research was conducted by distributing questionnaires to Startups in Medan, North Sumatera The testing is done empirically and consumers tend to lean on great communication and indication of a strong collaboration.